MODERN DIRECTIONS OF DEVELOPMENT OF CORPORATE CULTURE - SHPILEVA, Vira; BEZSIKERNYKH, Vladyslav; DUMANETSKYI, Viacheslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the article is a comprehensive analysis of modern directions of development of corporate culture in Ukraine, in particular in the conditions of martial law and challenges related to digitalization, flexible formats of work and socio-psychological aspects of well-being of personnel. The article deals with current trends in corporate culture in modern organizations, in particular in the context of digital transformation, the introduction of flexible formats of work and social and psychological challenges related to the care of the welfare and mental health of the staff. Particular attention is paid to the impact of martial law in Ukraine on changes in corporate culture, which require adaptability, inclusivity and maintenance of psychological safety of employees. The analysis of basic theoretical approaches and modern practices has been analyzed, key problems and prospects of development are identified. The article is aimed at forming a complex idea of the role of corporate culture as a factor of stability and efficiency of organizations in the conditions of constant changes and challenges. The directions of development of corporate culture, which is valuable to companies in the conditions of rapid adaptation to changes, is systematized and characterized. The experience of Ukrainian companies using modern corporate culture methods in their work and adapted corporate culture is generalized, switching to hybrid work models. It has been proven that modern Ukrainian companies are increasingly introducing value-oriented management approaches, using corporate culture as a strategic resource. Such practices contribute to improving the efficiency of business processes, attracting skilled personnel and strengthening the employer brand.
Keywords: corporate culture; psychological safety; flexible work formats; staff well -being; martial law; adaptability; inclusion